Cultural and Business Barriers to Working with the German Market from the Perspective of a Czech Entrepreneur - Malikova, Eliza; Semenenko, Vadim; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor thesis investigates how cultural and organizational divergence affects the performance of Czech entrepreneurial ventures in the German market. Drawing on intercultural frameworks (Hofstede, Trompenaars, GLOBE) and the historical economic evolution of Czech–German relations, the research identifies communication codes, temporal and procedural norms, hierarchical configurations, and trust formation mechanisms as key variables governing bilateral business interaction. Empirical evidence comes from six semi-structured interviews with Czech and German specialists. Results demonstrate systematic mismatches. The thesis evaluates current mitigation practices, including rigorous project planning and targeted intercultural training, and formulates evidence-based recommendations for Czech firms on direct communication, hierarchical navigation, and strategic value-chain positioning.
Vedoucí práce: Vadim Semenenko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses